2018
DOI: 10.1016/j.jad.2017.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and overlap of attention and memory biases in depression

Abstract: Our study showed that, across different paradigms and psychological measures, memory bias (and not attentional bias) represents a primary mechanism in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 75 publications
(93 reference statements)
8
50
2
Order By: Relevance
“…Another important finding from the current study was that negative attention bias, measured with reaction time or eye tracking, was not reliably associated with any of the depression symptoms. This finding is consistent with prior work documenting that negative attention bias (in contrast with memory bias) measured with different approaches was not strongly correlated with symptom severity across four studies involving 463 adult participants Association between negative 34 (Marchetti et al, 2018). Similarly, in a study that used best subsets regression to identify SRET and dot-probe metrics associated with concurrent depression severity, number of positive and negative words endorsed from the SRET were the best predictors of total score depression severity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another important finding from the current study was that negative attention bias, measured with reaction time or eye tracking, was not reliably associated with any of the depression symptoms. This finding is consistent with prior work documenting that negative attention bias (in contrast with memory bias) measured with different approaches was not strongly correlated with symptom severity across four studies involving 463 adult participants Association between negative 34 (Marchetti et al, 2018). Similarly, in a study that used best subsets regression to identify SRET and dot-probe metrics associated with concurrent depression severity, number of positive and negative words endorsed from the SRET were the best predictors of total score depression severity.…”
Section: Discussionsupporting
confidence: 89%
“…Further, cross-validated results found no reliable depression symptom predictors of negative attention bias, regardless if attention bias was measured with reaction time or eye tracking. These findings align with recent evidence suggesting that negative attention bias as measured with the dot-probe task may not track with concurrently measured depression symptom severity (Marchetti et al, 2018). Nevertheless, this study highlights the importance of cross-validating results and that negative self-referent processing (as measured with the SRET) may be most relevant for the maintenance of specific symptoms of depression, such as sadness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These pieces of evidence are of great interest, in that they could indicate a viable way to instill positive expectations about the future. Previous literature has shown that pessimism/hopelessness is strongly related to negative memory bias (Marchetti, Everaert, et al, 2018) and reduced capability to simulate one's own future is associated with diminished recall of specific personal memories (i.e., overgeneral autobiographical memory; Schacter, Addis, & Buckner, 2008;Williams et al, 1996). Hence, it is possible to speculate that targeting biased memory processing could help improving future expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies employing the extinction‐reinstatement model have provided valuable understandings into the neurobiology of drug addiction, although lacked one element of drug addiction in humans, ie, adverse consequences of drug‐seeking . To address this issue, which is of particular importance in the case of comorbid depression because of the cognitive bias towards negative information found in depressed patients, the “conflict model” developed in our lab was employed in the present study. This model allows measurement of cocaine abstinence and relapse in the SA procedure, where cocaine‐seeking behavior requires an adverse consequence of crossing an electrified grid floor.…”
Section: Discussionmentioning
confidence: 99%